Effects of Using Role-Play on Iranian Female EFL High School Students’ Speaking Performance, Anxiety and Motivation - Zahra Nouri; Elham Zarfsaz (International Journal of Practical and Pedagogical Issues in English Education)
The present study was conducted in order to investigate the effect of role-play technique on Iranian female junior high school students’ speaking ability, anxiety, and motivation. This research attempted to clarify whether or not using role-play activities in English classrooms and EFL contexts might enhance a more acceptable speaking ability and also motivation and decrease the anxiety of students in grade 8 in Nasle Payam Junior High School. To answer this question, 60 pre-intermediate students were selected through convenience sampling method. After homogenizing, finally 40 students were selected. Then, the participants were divided into experimental and control groups, 20 students in each group. A pre-test of speaking, speaking anxiety questionnaire (FLCAS), and speaking motivation questionnaire were administered to both groups. Then, the experimental group was instructed speaking through role-play technique while the control group was taught with respect to the existing methods. After two months of treatment, the post-test of speaking was administered in which the participants in both groups were asked to answer the posttest questions. Also, the questionnaires of anxiety and motivation were administered to students at the end of the treatment. The data obtained from this study was analyzed through ANCOVA. The results indicated that role-plays teaching technique has a significant effect on female EFL school learners’ speaking performance, however, it has not a significant effect on female EFL school learners’ speaking anxiety and motivation.